Youth Communication Savvy: Improving Their Ability to Become a Reliable Communicator in the Digital Era - Tiara, Andys; Mustika, Sri; Hariyati, Farida; Rahmawati, Yulia (Jogjakarta Communication Conference (JCC), 2025)
In the era of rapid digital transformation, teenagers face unique challenges in developing effective communication skills. Although they are digital natives, many adolescents lack the competence and awareness needed to communicate ethically and responsibly in both online and offline contexts. This community service activity aimed to strengthen the communication abilities of teenagers at Al-Ikhlas Jatipadang Mosque, South Jakarta. The program involved a series of steps, including situation analysis, planning, and implementation through counseling and practical exercises. Participants were introduced to the fundamentals of communication, the importance of polite behavior, and the principles of intelligent speech. They were also taught to recognize and correct common misconceptions—such as believing that communication is merely speaking or that it only occurs during intentional interaction. Practical sessions, including simulations of responding to online comments, helped reinforce the lessons. The results showed a significant improvement in participants’ understanding and communication skills, as indicated by pre- and post-test scores and participant feedback. The activity not only equipped teenagers with essential skills for navigating the digital world but also emphasized the importance of ethical communication, empathy, and social responsibility. The program highlights how community-based education can foster youth as positive communicators in society.